DYNAMICS OF GLYCEMIC CONTROL AFTER RENAL DENERVATION IN PATIENTS WITH RESISTANT HYPERTENSION AND TYPE 2 DIABETES MELLITUS - A. Yu. Falkovskaya; V. F. Mordovin; S. Ye. Pekarsky; A. Ye. Bayev; G. V. Semke; T. M. Ripp; Ye. S. Kravtchenko; I. V. Zyubanova (Бюллетень сибирской медицины)
The aim of the study was to evaluatetheglycemic control dynamics depending on degree of blood pressure (BP) reduction and dynamic of TNF-α after 6 and 12 months of Tran catheter renal denervation (TRD) of patients with true resistant hypertension (RH) and type 2 diabetes mellitus (T2DM). Material and methods. Thirty two essentially hypertensive patients with type 2 diabetes mellitus (T2DM) and resistant hypertension were included in single-arm prospective interventional study. Office BP measurement, ambulatory 24-h BP, renal Doppler ultrasound and assessment of renal function (proteinuria, creatinine, eGFR), HbА1c and fasting plasma glucose (FPG) levels, activity of TNF-α were performed at baseline and 6 and 12 months after TRD. On average, patients were taking 4 (3–6) antihypertensive drugs. None of the patients changed the antihypertensive treatments during follow-up. A 6 months follow-up was completed by 27 patients (43–75 years old, 14 male), 12 months follow-up was completed by 26 patients. Results. Renal denervation significantly reduced the systolic office BP (SBP) as well as 24-h SBP (– 27.2/–10.7 mm Hg and–13.4/–10 mm Hg, respectively, p < 0.01 after 6-month follow-up, and –31,7/–12,8 mmHg and –13.4/–10 mm Hg, respectively, p < 0.01 after 12-month follow-up) without any negative effect on renal function. The number of responders with reduction of SBP >10 mmHg according to ABPM were 56% (15/27) after 6-month and 61.5% (16/26) after 12-month follow-up. There were significant reduction of the average HbA1c levels (from (6.9 ± 1.8)% to (5.8 ± 1.5)%, p = 0.04) and nonsignificant decreasing of FPG levels (from 8.7 ± 2.8 to 7.7 ± 2.1 mmol/L, p = 0.07) after 6-month followup. Conspicuously, the responders according to ABPM had significantly higher mean dynamics of HbA1c than the non-responders after 6-month follow-up (–2.4 ± 1.9 and –0.1 ± 0.8%, p = 0.02, respectively) as well as after 12-month follow-up (–0.12 ± 0.98 and 1,26 ± 1.11%, p = 0.04 for HbA1c, and – 0.89 ± 1.9 и 0.85 mmol/L ± 1.19, p = 0.02 for FPG levels). There were significant decreasing of TNF-α after 12-monthfollow-up (from 2.21 (1.54–3.65) to 1.4 (1.11–1.47pg/ml), p = 0.007), without relation to BP and HbA1c dynamics, and response to TRD. There were not the correlations between dynamics of HbA1c and FPG levels with BP reduction and change of TNF-α after 12-month follow-up. Conclusions. Renal denervation of patients with true resistant hypertension and diabetes mellitus type 2 after 6 and 12 months was followed by improved glycemic control, BP reduction and decreasing of mean levels of TNF-α. Glycemic control improvement after the renal denervation was more expressive in the responders.